A bilayered scaffold based on RGD recombinant spider silk proteins for small diameter tissue engineering. Issue 2 (27th October 2014) - Zhang, Chao‐ying; Zhang, Da‐chun; Chen, Deng‐long; Li, Min
Abstract : A bilayered scaffold was fabricated via electrospinning layer‐by‐layer with the inner layer composed of blend fibers of spider silk protein and gelatin (pNSR16/Gt), then the polyurethane (PU) layer on the outside. The physicochemical and biological performance of scaffold were investigated. The pNSR16/Gt‐PU composite nanofibers with interconnected pores was detected a porosity of 88.7 ± 1.5%; with mechanical properties, including an appropriate permeability of 6.8 ± 0.2 ml min −1 cm −2, breaking strength (24.6 ± 3.6 MPa) and elasticity up to 145 ± 3.8% strain, and burst pressure reached 276 ± 7.1 kPa as well as an accepted suture retention strength (4.9 ± 0.8 N), optimized to mimic the nature artery. The pNSR16/Gt‐PU bilayered scaffold also proved to be capable to support cell growth and proliferation of Sprague‐Dawley rat aortic endothelial cells by 242 ± 10% (7 days vs. control). After all, the intimal surface promotes endothelialization and being highly anti‐thrombogenic, while the mismatch in mechanical properties outside induces intimal hyperplasia, it is desirable to develop a bioactive material with improved mechanical properties for small‐diameter vascular graft. POLYM. COMPOS., 37:523–531, 2016. © 2014 Society of Plastics Engineers